Development of grade 10 students’ modelling skills on circulatory system through model-based learning - Kullasatree Manee; Prasart Nuangchalerm (CV. FOUNDAE, 2023)
Aim: This study aims to elevate the modelling skills of Grade 10 students in understanding the circulatory system, using model-based learning, to a level where they can achieve at least a 70% passing score on a relevant unit test.Method: The study involved 23 students and implemented a model-based learning approach. Research tools included a design for model-based learning, assessments of the modelling process, a modelling ability exam, structural interviews, and student diaries. Data analysis was conducted using percentages and averages, and the action research was structured into two iterative rounds.Results: Initial findings from the first cycle revealed an average modelling ability score of 18.21 out of 24 (75.87%), with 14 students surpassing the 70% threshold. The second cycle showed marked improvement, with an average score of 19.94 out of 24, translating to an 83.09% success rate. Notably, all 23 students exceeded the 70% benchmark in this cycle.Conclusion: The implementation of model-based learning significantly enhanced the students' modelling skills in understanding the circulatory system. The method proved effective in not only achieving but surpassing the targeted 70% success threshold, demonstrating its potential as a valuable educational tool in biology.